Rodzina dotknięta przemocą – możliwości i formy pomocy na podstawie badań Specjalistycznych Ośrodków Wsparcia dla Ofiar Przemocy w Rodzinie w regionie dolnośląskim - Świątek, Beata (Karkonoska Państwowa Szkoła Wyższa, 2011)
One of the factors determining a family's capability is violence. It influences the quality of the offspring upbringing, family relationships and bonds. In its air social competence of parents declines and their attitude to family-related responsibilities deteriorates. The issue of domestic violence is tackles by specialists of the area of law, psychology, sociology, pedagogy and medicine, who are studying sources and methods of fighting with this phenomenon. Its social damage is so devastating that its unambiguous definition is almost impossible. In the face of a serious threat generated by domestic violence in recent years, there have been held campaigns, workshops, local and nationwide conferences to promote assistance to violence-stricken victims. Preventive schemes have also been developed to restrain violence in schools and local community. Violence affected individuals can seek help in centers founded especially for this purpose and maintained by local councils (MOPS) or county councils (PCPR), as well as non-government organizations and associations. A comprehensive support for families suffering from domestic violence is provided by Emergency InterventionCenters and Specialist Centers of Support for Victims of domestic Violence. In the region of Lower Silesia there exist two institutions of such a character, one inWroclaw and the other one in Walbrzych. Their activity involves therapeutic tasks, aid and provision for victims of domestic violence.
Keywords: rodzina; przemoc; Dolny Śląsk